Impact of artificial intelligence on task performance and perceived task load: a pragmatic randomized experiment - Bhadila, Ghalia Y.; Bahdila, Dania; Saber, Nujud O.; Alyafi, Dana A. (Frontiers in Education, 2026)
IntroductionThis study aimed to assess the impact of artificial intelligence (AI) assistance on immediate task performance and evaluate perceived task load and AI acceptance among dental interns in an educational setting.MethodsA pragmatic experiment was conducted among 132 dental interns during the 2024–2025 academic year. Participants were randomly allocated to either an AI-assisted group (n = 67) or a baseline knowledge control group (n = 65) to complete a 15-question quiz based on pediatric orthodontic cases. Perceived task load was measured using the National Aeronautics and Space Administration Task Load Index. AI acceptance was assessed using the Technology Acceptance Model (TAM). Task performance (quiz scores), task load, and AI acceptance were analyzed using Wilcoxon rank-sum tests and an adjusted generalized regression model.ResultsThe AI-assisted group achieved higher task performance scores (median, 13 vs. 11; p < 0.0001) and lower perceived task load scores (median, 21.7 vs. 41.7; p < 0.0001) than the control group. The AI-assisted group had 1.67 times higher odds of answering a question correctly compared to controls in the adjusted model. Responses to the TAM demonstrated high levels of perceived usefulness, perceived ease of use, and behavioral intention (Cronbach’s α = 0.92–0.95).ConclusionThe AI-assisted group demonstrated improved immediate task performance and reduced perceived task load compared to the control group. This study serves as a preliminary step toward understanding how AI tools can support clinical learning and decision-making processes in educational settings.